The Beauty and Richness of Yesenin's Lyrics - Khudaiberdieva Dilfuza Mukhtarovna (Genius Journals, 2022)
Yesenin's poetry, surprisingly "earthly", close to everyone, real to its very roots and at the same time "universal", universal, is illuminated by the unfading light of true love "to all living things in the world." It would seem that everything has already been said about Yesenin's work. And yet, every person, opening a volume of his poems, opens his Yesenin
Keywords: epithets; comparisons; metaphors; folk speech